Correlation of Motivation to Learn Arabic Language with Interest in Communication in Arabic Language of Students Department of Arabic Language Education Faculty of Tarbiyah Islam University of Zainul Hasan Genggong - Ainur Rofiq Sofa (Departement of Mathematics Education, 2023)
Study This motivated by the reduction Power pull and lower PBA ability of students major in communicate with Language Arabic , finally party Faculty nor Major do various method For increase it . Analyzed problem are : what and how motivation Study Language arabs and students and whether There is significant relationship _ between motivation Study with try communicate in Language arabic ?. For answer problem the collected data through questionnaire to 80 respondents , then analyzed in a manner descriptive , qualitative with percentage contingency and correlation . The result show that motivation Study student Arabic are below tall with percentage 84.40 % meanwhile get ranking sufficient communication tall with percentage of 78.80%. But percentage both of them No Far different . Analysis results correlation contingency show No There is significant correlation between motivation Study Language Arab with effort For get communication Language Arab student .